English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

How to figure out the first five terms term in an arithmetic ande geometric sequence and solve?

1. arithmetic, a sub2 = -2, d= -5 (Do I subtract -5 from -2 to get first term?

2. geometric, a sub 2 = -2, a sub 3 = -3 (How do I determine the common ration?)

Many thanks for your help!

2006-11-23 12:26:16 · 6 answers · asked by mdetaos 3 in Science & Mathematics Mathematics

6 answers

1) Yup. a_1 - 5 = a_2, so a_1 must be 3.
2) What does the common ratio actually mean? Its any term divided by the term before it. So in this case, the common ratio is just (-3)/(-2) = 1.5. Now, how would you get the first term? To go from the first term to the second you'd multiply by 1.5; thus to go from the second to the first, divide by 1.5: -2/1.5 = -4/3 is the first term.

2006-11-23 12:29:57 · answer #1 · answered by stephen m 4 · 2 0

You are correct about the first part, as long as you know that subtracting a negative number is is like adding the positive.

In a geometric sum, one term is multiplied by another to get the next term. In this case, -2 times something = -3. That can be written as -2x=-3. Now it's just solve for x. x=-3/-2 or 1.5. That being know we can now work backwards.

Something times 1.5 = -2.
1.5x=-2 x=-2/1.5 x=-1.333 with a line over the threes or -4/3.

The first term is -4/3.

2006-11-23 12:35:51 · answer #2 · answered by krbmeister 2 · 0 0

an = a1 + (n - 1)d
a2 = a1 + (2 - 1)(-5)
-2 = a1 + 1(-5)
-2 = a1 - 5
a1 = 3

Using this you get

an = 3 - 5(n - 1)

a1 = 3 - 5(1 - 1) = 3 - 5(0) = 3 - 0 = 3
a2 = 3 - 5(2 - 1) = 3 - 5(1) = 3 - 5 = -2
a3 = 3 - 5(3 - 1) = 3 - 5(2) = 3 - 10 = -7
a4 = 3 - 5(4 - 1) = 3 - 5(3) = 3 - 15 = -12
a5 = 3 - 5(5 - 1) = 3 - 5(4) = 3 - 20 = -17

-------------------------

an = a1 * r^(n - 1)

a2 = a1 * r^(2 - 1)
-2 = a1 * r^1
a1 = (-2/r)

a3 = a1 * r^(3 - 1)
-3 = a1 * r^2
a1 = -3/(r^2)

Now just set the 2 equal to each other.

(-2/r) = (-3/(r^2))

cross multiply

-2r^2 = -3r

divid both sides by r

-2r = -3

divide both sides by -2

r = (3/2)

Using that you get

Now plug this in for r into the equation a1 = (-2/r)

a1 = -2/(3/2)
a1 = (-2/1)/(3/2)
a1 = (-2/1)*(2/3)
a1 = (-4/3)

and now you have

an = (-4/3) * (3/2)^(n - 1)

a1 = (-4/3) * (3/2)^(1 - 1) = (-4/3)(3/2)^0 = (-4/3) * 1 = (-4/3)
a2 = (-4/3) * (3/2)^(2 - 1) = (-4/3)(3/2)^1 = (-4/3)(3/2) = -2
a3 = (-4/3) * (3/2)^(3 - 1) = (-4/3)(3/2)^2 = (-4/3)(9/4) = -3
a4 = (-4/3) * (3/2)^(4 - 1) = (-4/3)(3/2)^3 = (-4/3)(27/8) = (-9/2)
a5 = (-4/3) * (3/2)^(5 - 1) = (-4/3)(3/2)^4 = (-4/3)(81/16) = (-27/4)

If you like, you can put the answers in Mixed Fractions

Go to www.ltcconline.net/greenl/Courses/103B/seqSeries/ARITSEQ.HTM
and
www.mathguide.com/lessons/SequenceGeometric.html

to see where i got my help from.

2006-11-23 14:48:43 · answer #3 · answered by Sherman81 6 · 1 0

it really is an mathematics progression so sum is (first + very last) x (0.5 the shape of words) yet first we favor to comprehend the way many words there are sixty seven = 18 + 7(n - a million) => 40 9 = 7(n - a million) => n = 8 Sn = (18 + sixty seven) x 4 = 80 5 x 4 = 340 i do not comprehend what 'locate the sum of the first 4 words contained in the sequence of 2n-a million' ability, although.

2016-11-29 10:06:46 · answer #4 · answered by endicott 4 · 0 0

set up the equation first: a sub n = d(n-1)+a1
you know a sub 2 is -2 and d is -5 so sub -2 for a sub n and -5 for d
we have: -2= -5(n-1)+a1
given that -2 is in second position so 2 for n
-2= -5(2-1)+a1
-2= -5(1)+a1
-2= -5+a1
a1=3

2006-11-23 12:40:52 · answer #5 · answered by      7 · 0 0

are you only given those two terms? and what is d= -5?

2006-11-23 12:30:35 · answer #6 · answered by nanabanana 2 · 0 0

fedest.com, questions and answers